SCREENING FITOKIMIA DAN AKTIVITAS ANTIRADIKAL BEBAS EKSTRAK METANOL DAUN GAHARU (Gyrinops versteegii) - Mega, I Made; Swastini, Dewa Ayu (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010)
It has been done screening fitokimia and the determination of free antiradical activity extract methanol of gaharu leaf. The screening fitokimia determined by the colour test and free antiradical activity determined by diphenyl pykril hydrazil (DPPH) method according to sphectrophotometry UV-Vis, before that the honey was diluted with methanol and then the absorbance was measured on 497nm, 517 nm, and 537 nm. The result showed that methanol extract of gaharu leaf contain phenol, flavonoid and terpenoid compound and the free antiradical activity showed inhibitor percent is 106,32 % (5”) and 111,31 % (60’).
Keywords: anti-freeradical activity, DPPH method, gaharu, fitochemistry screening